A Case of Rare Complication of Inguinal Parietoplasty according to Lichtenstein: Entero Cutaneous Fistula. (17th January 2018) - Kouakou, K. B.; Anzoua, K. I.; Traore, M.; Leh, B. K. I.; N'Dri, A. B.; Ekra, A. S.; Kouakou, B. A.; Lebeau, R.; Diané, B.
Abstract : Lichtenstein intervention is currently the classic model of the regulated treatment of inguinal hernias by direct local approach. This "tension-free" technique satisfies both patients and practitioners. However, it does not often evade severe complications of parietal surgery. The authors report their treatment experience in rural Africa of a late enterocutaneous fistula which aggravated an inguinal hernia repair according to the Lichtenstein procedure. Physiopathology, diagnosis, and treatment of that disease are analyzed in the light of literature.